Water Energy Nexus and Energy Transition—A Review - Helerea, Elena; Calin, Marius D.; Musuroi, Cristian (MDPI AG, 2023)
The new perspectives of the water–energy nexus, water-for-energy and energy-for-water, emphasize the current and future need to find ways to produce as much energy with as low an amount of water as possible and to obtain as much water with as little energy as possible. In order to promote and implement the concept of sustainable development, the understanding of the dynamic and complex relationship between water and energy is crucial, especially in the context of energy transition. This paper presents a comprehensive analysis of the recent approaches regarding water and energy and the interlink during implementation, operation and servicing of various water and energy production systems. This endeavor is placed in the context of current energy transition from fossil fuels to renewable energy sources. A qualitative and quantitative analysis is performed with various literature solutions from water-for-energy and energy-for-water perspectives for a broader view of the impact of implementing novel technologies in terms of resource use. Technological and managerial innovations are discussed and placed in a transdisciplinary context with a focus on establishing key approaches for achieving sustainable development goals.
Keywords: water–energy nexus; energy-for-water; water-for-energy; energy transition; sustainable development goal; renewable energy; net zero emissions